Youth in the 21st century - Linares Delgado, Patricia Giuliana (2011)
Politics is a human, intersubjective activity, through which people participate in the affairs of their community. It has been present since times dating back to ancient Greece, where the inhabitants of the Polis were concerned with matters concerning the State. Politics at that time was considered an art, however, in our times, this concept has changed. It should be noted that each member of the community is a politician, but not all live from politics. This is the root of the problem of exclusion and lack of interest of young people in political affairs.